Nanocomposite polymer electrolytes comprising starch-lithium acetate and titania for all-solid-state supercapacitor - Ong, A.C.W. (Springer Science and Business Media Deutschland GmbH, 2021)
A nanocomposite solid polymer electrolyte (SPE) system has been prepared for application in a supercapacitor. Corn starch is used to host the ionic conduction with lithium acetate (LiOAc) salt as an ion provider. Different concentrations of nanosized titanium dioxide (TiO2) filler have been added to analyse the influence of nanofiller addition on the conductivity and other properties of the electrolytes. Structural characterisation and complex formation have been examined by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy, respectively. It is shown that the room temperature conductivity changes with the change in TiO2 concentration. Adding 4Â wt. TiO2 to the starch-LiOAc complex leads to an optimum conductivity of (8.37 Â± 1.04) Ã 10â4Â SÂ cmâ1. The variation in conductivity is accompanied by the change in surface morphology as observed from field emission scanning electron microscopy (FESEM) analysis. Linear sweep voltammetry (LSV) indicates that the electrochemical potential stability window of the electrolyte with 4Â wt. TiO2 lies in the range between â 2.0 and + 1.9Â V. A supercapacitor has been assembled using the electrolyte, and its performance has been characterised using impedance technique and cyclic voltammetry. Â© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.